2018
DOI: 10.6001/chemija.v29i1.3641
|View full text |Cite
|
Sign up to set email alerts
|

Properties and characterization of CZTS nanoparticles prepared by microwave heating irradiation

Abstract: Cu 2 ZnSnS 4 (CZTS) nanoparticles suitable for solar cell absorber fabrication were synthesized by the microwave-assisted heating method. The influence of the reaction temperature, the temperature increase duration and post-annealing temperature on the chemical composition, crystallographic structure, phase purity and optical properties of CZTS nanocrystals has been investigated by means of XRD, Raman spectroscopy, scanning (SEM) and transmission electron microscopies (TEM), EDX and UV-Vis spectroscopies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Where Hassanien et al, [22] reported the increase in crystallite size value from 4.5nm to 38.8nm for CZTS with an annealing temperature of 400 °C to 550 °C, Liping Chen et al, [23] observed the increase in crystallite size from 5.60nm to 19.97nm in CZTS when annealed from 250 °C to 550 °C, Giedrė Grincienė et al, [24] reported the size of crystallites increases from 2.4 to 24.1 nm for CZTS with the increase of annealing temperature from 300 °C to 550 °C. The decrease in microstrain and dislocation density with an increase in crystallite size implies a less number of lattice defects i.e.…”
Section: D= (Nm)mentioning
confidence: 99%
“…Where Hassanien et al, [22] reported the increase in crystallite size value from 4.5nm to 38.8nm for CZTS with an annealing temperature of 400 °C to 550 °C, Liping Chen et al, [23] observed the increase in crystallite size from 5.60nm to 19.97nm in CZTS when annealed from 250 °C to 550 °C, Giedrė Grincienė et al, [24] reported the size of crystallites increases from 2.4 to 24.1 nm for CZTS with the increase of annealing temperature from 300 °C to 550 °C. The decrease in microstrain and dislocation density with an increase in crystallite size implies a less number of lattice defects i.e.…”
Section: D= (Nm)mentioning
confidence: 99%
“…The band gap energies were obtained by plotting (αhυ) 2 as a function of hυ [47]. The band gap energy for CZTSe and CZTS are 1.0 eV and 1.5 eV, respectively [48][49][50]. The extrapolated absorption edges of the CZTSSe samples deposited from the DMF, DMSO, and H 2 O-EtOH solutions and annealed at a temperature of 540 °C correspond to 1.21, 1.29 and 1.31 eV band gap values, respectively.…”
Section: Optoelectrical Studies Of Cztsse Films Fabricated Using Diff...mentioning
confidence: 99%
“…In the last decade, copper-based quaternary semiconductor material Cu2ZnSnS4 (CZTS) was widely considered as a most promising absorber layer candidate for low-cost thin-film solar cells, owing to its high absorption coefficient (>10 4 cm -1 ) and optimal bandgap (1.0-1.5 eV) which are ideal properties for the application under solar irradiation. [1][2][3][4] .The compounds such as copper-zinc, tin-sulfur accompanied by non-toxic and friendly environmental solvents have many photovoltaic technology applications. 5,6 The features of these compounds make them suitable for widespread and low-cost applications in the thin-film solar cells.…”
Section: Introductionmentioning
confidence: 99%